Hubungan Beban Kerja Dengan Turnover Intention Pada Perawat Di Rumah Sakit Harapan Bunda Kota Batam Tahun 2020 - Yulia Devi Putri; Trisya Yona Febrina; Dwi Fadhila Rahma (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Turnover incidence can reach 60% per year where one of the causes of turnover is the high workload. The turnover that occurs is very detrimental to the company both in terms of costs, resources and employee motivation. The purpose of this study was to determine the relationship between nurses' workload and turnover intention in nurses with a cross sectional design. The implementation time starts on July 18-22 2020. The number of nurses in the study amounted to 35 nurses from the total population of 51 nurses because they were not included in the inclusion criteria. This study was analyzed using the Chi Square test. The measuring instrument of this research used questionnaires and interviews. The results of the study obtained 20 nurses (57.1%) with high workload and 18 nurses (51.25%) with high turnover intention. The results of the bivariate analysis showed that there was a relationship between workload and turnover intention of nurses in the inpatient room at Harapan Bunda Hospital, Batam City with p value = 0.001 <0.05. Nurses who have a high workload have a tendency to turnover compared to nurses who have a low workload. To prevent nurse turnover in hospitals, it is necessary to pay attention to the nursing management to pay attention to the workload of nurses.